A new hypogean Trechus Clairville (Coleoptera, Carabidae, Trechini) discovered in a non-calcareous Superficial Subterranean Habitat of the Iberian System (Central Spain) - Ortuño, Vicente M.; Cuesta, Eva; Gilgado, José D.; Ledesma, Enrique (Zootaxa, 2014)
A new hypogean species of Trechus Clairville, Trechus arrecheai sp. nov., is described from the Iberian Peninsula. It was captured by subterranean pitfall traps in a non-calcareous Superficial Subterranean Habitat from the Moncayo Massif (Zaragoza, Spain). Data on the accompanying fauna are provided and the biogeographical implications of this discovery are discussed. A synthesis of the data about the known distribution of the Trechus angusticollis species group is provided.